Impact of Location on Predator Control Preference Patterns - Stanger, Melissa E.; Slagle, Kristina M.; Bruskotter, Jeremy T. (Frontiers in Conservation Science, 2022)
In recent decades, interactions with carnivores have increased in suburban and urban areas. However, it is unknown how predator control preferences of urban and suburban residents compare. We sought to characterize predator control preferences regarding interactions with bobcats (Lynx rufus) and coyotes (Canis latrans), and compare these preferences among people living in urban, suburban, and rural areas. We also sought to determine the factors that predicted the likelihood of respondents changing their predator control preference. We conducted cross-sectional surveys of adult residents of the United States and the state of Ohio and embedded randomly assigned carnivore interaction scenarios in which respondents were asked to choose their preferred predator control in response to each scenario. We found that when both scenarios took place in an agricultural location, respondents became significantly more sensitive to changes in the severity, causing them to me more likely to switch predator control preferences. Subjects overwhelmingly indicated a preference for non-lethal forms of predator control. Specifically, 71.8% of respondents preferred non-lethal in response to both scenarios, 18.5% gave mixed responses (i.e., preferred lethal in response to one of the scenarios but non-lethal in response to the other scenario), and only 9.7% preferred lethal predator control in response to both scenarios. The tendency to prefer only non-lethal methods decreased along the urban-rural gradient such that 78.5% of urban respondents expressed a consistent preference for non-lethal forms of control, compared with 72.8% of suburban respondents, and 51.3% rural respondents. This suggests that most urban and suburban residents view lethal predator control methods as simply inappropriate—at least for the scenarios described. In practice, the management of human-carnivore interactions in urban and suburban areas is complicated by a variety of factors (e.g., the presence and density of humans and their pets) which reduce the flexibility of wildlife managers in these areas. Additionally, management options may be further restricted by the preferences of residents, especially given that management is likely to be more visible in these areas. Strong preferences against lethal control in urban and suburban settings may incentivize the development of novel methods for controlling human-carnivore conflicts in the future.